Dual Sympathetic Input into Developing Salivary Glands. (September 2019) - Teshima, T.H.N.; Tucker, A.S.; Lourenço, S.V.
Neuronal signaling is known to be required for salivary gland development, with parasympathetic nerves interacting with the surrounding tissues from early stages to maintain a progenitor cell population and control morphogenesis. In contrast, postganglionic sympathetic nerves arrive late in salivary gland development to perform a secretory function; however, no previous report has shown their role during development. Here, we show that a subset of neuronal cells within the parasympathetic submandibular ganglion (PSG) express the catecholaminergic marker tyrosine hydroxylase (TH) in developing murine and human submandibular glands. This sympathetic phenotype coincided with the expression of transcription factor Hand2 within the PSG from the bud stage (E12.5) of mouse embryonic salivary gland development. Hand2 was previously associated with the decision of neural crest cells to become sympathetic in other systems, suggesting a role in controlling neuronal fate in the salivary gland. The PSG therefore provides a population of TH-expressing neurons prior to the arrival of the postganglionic sympathetic axons from the superior cervical ganglion at E15.5. In culture, in the absence of nerves from the superior cervical ganglion, these PSG-derived TH neurons were clearly evident forming a network around the gland. Chemical ablation of dopamine receptors in explant culture with the neurotoxin 6-hydroxydopamine at early stages of gland development resulted in specific loss of the TH-positive neurons from the PSG, and subsequent branching was inhibited. Taken altogether, these results highlight for the first time the detailed developmental time course of TH-expressing neurons during murine salivary gland development and suggest a role for these neurons in branching morphogenesis.